Subjective Assessment of Motor Function by the Bedside Nurses in Mechanically Ventilated Surgical Intensive Care Unit Patients Predicts Tracheostomy. (February 2023) - Friedrich, Sabine; Teja, Bijan; Latronico, Nicola; Berger, Jay; Muse, Sandra; Waak, Karen; Fassbender, Philipp; Azimaraghi, Omid; Eikermann, Matthias; Wongtangman, Karuna; ,
Objective: In many institutions, intensive care unit (ICU) nurses assess their patients' muscle function as part of their routine bedside examination. We tested the research hypothesis that this subjective examination of muscle function prior to extubation predicts tracheostomy requirement. Methods: Adult, mechanically ventilated patients admitted to 7 ICUs at Beth Israel Deaconess Medical Center (BIDMC) between 2008 and 2019 were included in this observational study. Assessment of motor function was performed every four hours by ICU nurses. Multivariable logistic regression analysis controlled for acute disease severity, delirium risk assessment through the confusion assessment method for the ICU (CAM-ICU), and pre-defined predictors of extubation failure was applied to examine the association of motor function and tracheostomy within 30 days after extubation. Results: Within 30 days after extubation, 891 of 9609 (9.3%) included patients required a tracheostomy. The inability to spontaneously move and hold extremities against gravity within 24 h prior to extubation was associated with significantly higher odds of 30-day tracheostomy (adjusted OR 1.56, 95% CI 1.27−1.91, p < 0.001, adjusted absolute risk difference (aARD) 2.8% (p < 0.001)). The effect was magnified among patients who were mechanically ventilated for >7 days (aARD 21.8%, 95% CI 12.4−31.2%, p-for-interaction = 0.015). Conclusions: ICU nurses' subjective assessment of motor function is associated with 30-day tracheostomy risk, independent of known risk factors. Muscle function measurements by nursing staff in the ICU should be discussed during interprofessional rounds.